Kedudukan Hukum RUPS Pada Perusahaan Holding Company di Indonesia - Aulia Puspa Andari; Priscilla Regina Pramesti Wibawa; Sumriyah Sumriyah (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
The Holding Company is part of the company, the Holding Company Philosophy which was originally to create added value, efficiency and strengthen the supply chain has now become a business innovation for the company's development in Indonesia. Because the Holding Company is part of the Company, the highest position in the company is the GMS. The position of the GMS in the holding company has the same role as in the company, namely making strategic decisions, overseeing company performance, and maintaining transparency and accountability even though the holding company itself is a holding company which under its control oversees the policies of the subsidiary companies it shelters.